Warfighter Acceptance of Future Physio-Behavioral Monitoring and Augmentation: Update. (September 2017) - Funke, Gregory J.; Best, Christopher; Menke, Lauren E.; Strang, Adam J.
Strategic military guidance suggests adaptive automation as an augmentation strategy to enhance operator performance. This approach is predicated on operator consent to monitoring. A recent investigation of these issues indicated that operators were accepting of monitoring, but responses may have been influenced by perceptions of how data would be used. Purposes for the current study were to explicitly address that issue and expand on the topics covered with operators. Sixteen operators completed an updated version of the Device Comfort Questionnaire, a measure designed to survey operators regarding their acceptance of monitoring and several potential augmentation strategies. The results of the survey suggested that operators were more positive about monitoring by human military commanders, and generally neutral to all other topics addressed. However, impartiality is not endorsement of those technologies – operators will need to be convinced of their utility if they are to be successfully deployed in the future.